The impact of self-generated and explicitly acquired contextual knowledge on anticipatory performance - Magnaguagno, L.; Hossner, E.-J. (Journal of Sports Sciences, 2020)
The present study aimed to investigate the impact of self-generated and explicitly acquired contextual knowledge of teammates` defensive qualities on anticipatory performance in a complex sensorimotor task. Twelve expert and twelve near-expert handball players were examined in a domain-specific defence task presented in an immersive virtual-reality environment. In two-thirds of the trials, 1:1 situations (i.e., teammate versus opponent) were presented in which the teammates next to the participant played a specific role. Whilst the weak teammate lost every situation, which required the participant to block a throw, the strong teammate won every situation, which required the participant to stay in his position. Since explicit knowledge of this pattern was only provided in a later phase of the experiment, participants would have to generate the respective knowledge themselves beforehand. To this end, the following variables were analysed: the detection of experimentally induced patterns, the correctness of the participants` motor responses and their positioning as a function of the respective teammate`s defensive quality. Main results showed that experts are better able to utilize both self-generated as well as explicitly acquired knowledge regarding teammates` defensive qualities, whereas near-experts` performance was enhanced only by explicitly provided contextual knowledge.